Distribuição dos elementos Si, Al, Fe, Ca, Mg, Mn, Ti, Cu, K e Na em solos desenvolvidos na região do granito central da Serra dos Carajás - sul do estado do Pará - DAMOUS, Nina Rosa Leal (Universidade Federal do Pará, 2017)
The distribution of elements in the weathered pro rocks is effected mainly by climate, geomorphology and parent material. The present study deals with the distribution of Si, Al., Fe, Ca, Mg, Mn, Ti, Cu, K and Na in the weathered products of the Central Gravite at Serra dos Carajas - Para, Brazil, which occurs in an area which is characterized by ondulated relief and humid tropical climate. Samples representing two selected weathering profiles were collected to depths that did not exceed 6 m. The analytical treatment consisted of poten/biometric determinations of pH values, the determination of the chemical and mineralogical compositions of the sand, silt and clay fractions, and the determination of the chemical composition of the oxide fraction. The two profiles reveal an intensa process of feldspar removal from the parent granite and the formation of a sand-clayey lato-soil. In this process quartz has been preserved and clay minerals and aluminium and iron hidroxides have been formed constituting the dominant assemblage of the soil. Ca, Mg, Mn, Na and K from the parental rock were nearly completely leached away to the extent that these elements are only found in small amounts in the remaining feldspars or adsorbed on clay minerals. On the other hand, Ti present principally in resistant minerals, practically maintains its' original concentration. Cu is sligthly enriched in the profiles due to adsorption in the clay minerals. The presence of only very small amounts of feldspar along the profiles shows the great intensity of the weathering process acti.ng on the granitic rocks. The direct transformation of feldspar to clay minerals or aluminium oxides is related to the climatic conditions frainy and dry seasons) prevalent in the area.